2022
DOI: 10.3389/fcell.2022.931082
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Therapeutic Properties of Exosomes in Cardiac Fibrosis

Abstract: Cardiac fibrosis results from both the differentiation of cardiac fibroblasts and excessive accumulation of extracellular matrix (ECM), leading to myocardial stiffness and reduced compliance of the ventricular wall. The conversion of cardiac fibroblasts to myofibroblasts is the most important initiating step in the process of this pathological cardiac remodeling. It occurs during the progression of many cardiovascular diseases, adversely influencing both the clinical course and outcome of the disease. The path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…There is mounting evidence that EVs can be used to diagnose myocardial fibrosis [ 73 , 74 ]. Wang et al [ 75 ] identified that the level of EV carried miR-425 and miR-744 in plasma could represent the progression of fibrosis in HF.…”
Section: Mechanisms Of Evs In Fibrotic Diseasesmentioning
confidence: 99%
“…There is mounting evidence that EVs can be used to diagnose myocardial fibrosis [ 73 , 74 ]. Wang et al [ 75 ] identified that the level of EV carried miR-425 and miR-744 in plasma could represent the progression of fibrosis in HF.…”
Section: Mechanisms Of Evs In Fibrotic Diseasesmentioning
confidence: 99%
“…In cardiovascular diseases, circulating EVs miRNAs, miRNA-425, and miRNA-744 acts as a novel biomarkers for cardiac fibrosis [231,232]. Also, miR-30d is associated with deleterious cardiac remodeling and the expression of fibrosis and…”
Section: Nucleic Acid As Diagnostic and Prognostic Biomarkermentioning
confidence: 99%